A Nematode of the Mid-Atlantic Ridge Hydrothermal Vents Harbors a Possible Symbiotic Relationship - Bellec, Laure; Cambon-Bonavita, Marie-Anne; Cueff-Gauchard, Valérie; Durand, Lucile; Gayet, Nicolas; Zeppilli, Daniela (Frontiers in Microbiology, 2018)
Deep-sea hydrothermal vent meiofauna have been the focus of recent research and the discovery of an abundant well-adapted free-living marine nematode on the Mid-Atlantic Ridge offers new perspectives on adaptations to the vent environment. Indeed, knowledge concerning biological interactions of microbes and meiofauna in marine extreme environments is scarce, especially for nematodes. In this study, we used microscopic observations (FISH and SEM) and metabarcoding of 16S rRNA to characterize the bacterial community of the nematode species Oncholaimus dyvae, an overlooked but ecologically important vent organism. Detection of bacteria in the buccal cavity and on the cuticle (SEM) and epibionts in its intestine (FISH) suggests that O. dyvae harbors its own bacterial community. Molecular results and phylogenetic analysis show that bacteria associated with this species are related to symbiotic lineages typical of hydrothermal vent fauna, such as sulfur-oxidizing bacteria related to Epsilonproteobacteria and Gammaproteobacteria. This multi-approach study suggests a potential symbiotic role of bacteria with its nematode host and opens new research perpectives on vent meiofauna.